Pengaruh Penerapan Video Tutorial CAD Pembuatan Pola Blus terhadap Peningkatan Kompetensi Mahasiswa - Irmayanti, Irmayanti Irma; Hamidah, Hamidah; Achmadi, Taofan Ali (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2020)
CAD technology for the fashion industry is used, from determining the type and pattern of materials, sizes, and making patterns to the percentage of products, so that computers are one of the important components in the fashion industry. Therefore, to support the growth of the fashion industry in the country, reliable and skilled human resources (HR) are needed to keep up with the dynamic development of the fashion industry, including in the use of information technology and digital devices. Based on this, it is necessary to strive to increase the competence of students in mastery of making clothing patterns digitally. This study aims to determine the contribution of using video tutorials for making fashion patterns to increasing student competence in the CAD Course of Clothing Design in D3 PKK FT UNM Study Program. The research subjects included students who were in the fourth semester of D3 Fashion Design study program. The results showed that: (1) the average competency score of the experimental class students who used video tutorials was higher than the average competency scores of control class students who used conventional media in making blouse patterns using CAD RP-DGS, (2) The use of videos tutorial for making fashion patterns has a positive and significant effect on improving student competence as shown by the results of hypothesis testing using the t-test. This proves that the use of video tutorials as a learning medium in blouse pattern making using CAD RP-DGS is very useful in helping lecturers and students as an effort to achieve learning competencies in the CAD course for D3 Department of PKK FT UNM Department.